Protocol of the PROMOTE study: characterization of the microbiome, the immune response, and one-carbon metabolism in preconceptional and pregnant women with and without obesity (an observational subcohort of the Rotterdam Periconception cohort) - Nicole Schenkelaars; Lieske Wekema; Marijke M. Faas; Régine P.M. Steegers-Theunissen; Sam Schoenmakers (PLoS ONE, 2025)
Introduction Preconceptional and maternal obesity are well-known risk factors for pregnancy and fetal complications including gestational diabetes, hypertensive disorders, and macrosomia. Maternal obesity is associated with offspring obesity and increased healthcare costs. To disrupt the cycle of obesity, we aim to investigate the impact of the composition of the maternal microbiota (bacteria and viruses) throughout preconception and pregnancy and the associations with the immune responses and one-carbon metabolism (1-CM) as an underlying mechanism in the pathophysiology of increased adverse pregnancy outcomes in maternal obesity. Methods and analysis The PROMOTE study is a subcohort of the Rotterdam Periconceptional Cohort, a hospital-based observational cohort study. We will include 70 women per BMI group: ≥ 30 kg/m2 or 18.5-25 kg/m2, at different time points in each group: 10 preconceptional, 50 in the first trimester (with longitudinal follow-up during pregnancy, delivery and postpartum) and 10 in the third trimester of pregnancy. Which makes a total of 140 inclusions. Vaginal and rectal bacteriome, virome, and blood samples are collected. In the third trimester inclusions, only faecal samples are collected. Microbiota samples will be analysed using 16S rRNA sequencing. Bacteriome and virome profiles are compared between the BMI subgroups, associations with general immune responses and 1-CM markers will be shown. Trial registration ClinicalTrials.gov (NCT05754645)